2003
DOI: 10.1038/sj.ejhg.5201143
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism R92Q of the tumour necrosis factor receptor 1 gene is associated with myocardial infarction and carotid intima-media thickness – The ECTIM, AXA, EVA and GENIC Studies

Abstract: The TNFRSF1A gene was screened for polymorphisms in 95 subjects with premature myocardial infarction (MI), who also had one parent who had an MI. A total of 10 polymorphisms were found: three in the promoter region, two in exons and five in introns. All polymorphisms were genotyped in ECTIM, a case-control study of MI (1815 subjects). The nonsynonymous 92Q allele was found in 1.8, 1.0 and 1.7% of controls from Strasbourg, Belfast and Glasgow -respectively; in cases: 4.2, 2.2 and 3.2%. The populationadjusted od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
2
25
1
2
Order By: Relevance
“…Poirier et al used single-strand conformational polymorphism and sequencing analysis on only 26% of the total TNFR1 gene, predominantly on coding sequences, to identify CAD-associated TNFR1 SNPs, and subsequently found that the 92Q allele of TNFR1 (rs4149584) was associated with increased risk of MI among UK and French residents of European descent. Although we observed evidence of 92Q allele transmission to affected siblings in GENECARD, our CAD cases from CATHGEN and GENECARD did not demonstrate greater frequency of the 92Q allele than our controls, even though the absolute 92Q frequency in our cohorts was similar to that observed by Poirier et al in their control groups (1.6 -2%; Supplementary Material, Table S3) (11).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Poirier et al used single-strand conformational polymorphism and sequencing analysis on only 26% of the total TNFR1 gene, predominantly on coding sequences, to identify CAD-associated TNFR1 SNPs, and subsequently found that the 92Q allele of TNFR1 (rs4149584) was associated with increased risk of MI among UK and French residents of European descent. Although we observed evidence of 92Q allele transmission to affected siblings in GENECARD, our CAD cases from CATHGEN and GENECARD did not demonstrate greater frequency of the 92Q allele than our controls, even though the absolute 92Q frequency in our cohorts was similar to that observed by Poirier et al in their control groups (1.6 -2%; Supplementary Material, Table S3) (11).…”
Section: Discussionsupporting
confidence: 69%
“…Although these tests suggested only modest evidence for the association of TNFR1 with CAD, it is notable, nonetheless, that they suggest evidence for the association between CAD and the TNFR1 R92Q polymorphism-the SNP originally associated with MI, as found by Poirier et al (11) (P , 0.05; Supplementary Material, Table S2). Together, data from GENECARD and Poirier et al (11) support the association between CAD and TNFR1 discerned in CATHGEN. Moreover, in conjunction with CATHGEN older normal controls, our GENECARD data also support the association found in CATHGEN between two TNFR1 SNPs and aging-associated atherosclerosis (Supplementary Material, Table S1).…”
Section: Tnfr1 Single-nucleotide Polymorphisms Associate With Atherossupporting
confidence: 53%
See 2 more Smart Citations
“…The R92Q mutation has also been associated with clinical phenotypes other than TRAPS, such as early arthritis [34], Behçet's disease with extracranial deep vein thrombosis [47], atherosclerosis [48] or recurrent pericarditis [49]. These findings support the known fact that different inflammatory diseases share genetic susceptibility loci.…”
Section: R92q Mutation and Diseases Other Than Trapsmentioning
confidence: 61%